If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Ln(x + -4) = ln(x + -1) + -1ln(x + -5) Reorder the terms: nL(-4 + x) = ln(x + -1) + -1ln(x + -5) (-4 * nL + x * nL) = ln(x + -1) + -1ln(x + -5) (-4nL + nxL) = ln(x + -1) + -1ln(x + -5) Reorder the terms: -4nL + nxL = ln(-1 + x) + -1ln(x + -5) -4nL + nxL = (-1 * ln + x * ln) + -1ln(x + -5) -4nL + nxL = (-1ln + lnx) + -1ln(x + -5) Reorder the terms: -4nL + nxL = -1ln + lnx + -1ln(-5 + x) -4nL + nxL = -1ln + lnx + (-5 * -1ln + x * -1ln) -4nL + nxL = -1ln + lnx + (5ln + -1lnx) Reorder the terms: -4nL + nxL = -1ln + 5ln + lnx + -1lnx Combine like terms: -1ln + 5ln = 4ln -4nL + nxL = 4ln + lnx + -1lnx Combine like terms: lnx + -1lnx = 0 -4nL + nxL = 4ln + 0 -4nL + nxL = 4ln Solving -4nL + nxL = 4ln Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4ln' to each side of the equation. -4nL + -4ln + nxL = 4ln + -4ln Reorder the terms: -4ln + -4nL + nxL = 4ln + -4ln Combine like terms: 4ln + -4ln = 0 -4ln + -4nL + nxL = 0 Factor out the Greatest Common Factor (GCF), 'n'. n(-4l + -4L + xL) = 0Subproblem 1
Set the factor 'n' equal to zero and attempt to solve: Simplifying n = 0 Solving n = 0 Move all terms containing n to the left, all other terms to the right. Simplifying n = 0Subproblem 2
Set the factor '(-4l + -4L + xL)' equal to zero and attempt to solve: Simplifying -4l + -4L + xL = 0 Reorder the terms: -4L + -4l + xL = 0 Solving -4L + -4l + xL = 0 Move all terms containing n to the left, all other terms to the right. Add '4L' to each side of the equation. -4L + -4l + 4L + xL = 0 + 4L Reorder the terms: -4L + 4L + -4l + xL = 0 + 4L Combine like terms: -4L + 4L = 0 0 + -4l + xL = 0 + 4L -4l + xL = 0 + 4L Remove the zero: -4l + xL = 4L Add '4l' to each side of the equation. -4l + 4l + xL = 4L + 4l Combine like terms: -4l + 4l = 0 0 + xL = 4L + 4l xL = 4L + 4l Add '-1xL' to each side of the equation. xL + -1xL = 4L + 4l + -1xL Combine like terms: xL + -1xL = 0 0 = 4L + 4l + -1xL Simplifying 0 = 4L + 4l + -1xL The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
n = {0}
| 2(3x+4)=3(x+5) | | 6x^2+33xy+36y=0 | | 5(-x+4)-5x-5=105 | | (d-21)=105 | | y+2y+3z=26 | | 2x^5+16x^2=0 | | -4x-4=x+16 | | 24+42+48=4+2x-14 | | 2+11x=8x+7 | | -7-4u-15y=0 | | 3y-5(2x+2)=10 | | 8x-20=x+10 | | 2(4+4/12)=(5+11/12)x | | 144=2x+4(x+18) | | https://pisd1610-hs-ccl.gradpoint.com/Resource/7947561,0/Assets/testitemimages/algebra_2a/matrices/mc049-1.jpg | | 2-8=20 | | 8y-3=-133 | | -3-2y=5.5 | | 21+15=35+x+16 | | 9g-15=4h | | 9(x-2)+2=3x+6(-3+x) | | 5x-3(7x-9)=-69 | | 18=4x+3y | | y=8p^3-104p^2 | | 9(x-2)+2=3x+6x-3 | | h(t)=-16t^2+150t | | 2v^2+15=33 | | -103=7x+4(-6x+4) | | -7-8v=6v-7+8v | | 9x^2=576 | | y^2=350 | | 7x-3=3x+20 |